Factor that affecting carbon dioxide emission in developing countries / Nurul Athirah Azli - Azli, Nurul Athirah (Faculty of Business and Management, 2018)
The rising of carbon dioxide (C02) emissions has become a major threat to the worldwide environment. C02 emissions made up more than 80 per cent of the greenhouse gases released. An excellent growth on income requires firms to gain more and expand their businesses and this will lead to more carbon dioxide (C02) emissions. Researchers and scientists alike believe that the influence of C02 on global warming and climate change will continue in the future. The factors leading to C02 emission could contribute to solving the increasing trend level of C02 emissions. Thus, the major focus of this study is to investigate the determinants of C02 emission in developing countries. The data for this study will be collected using secondary data. The dependent variable for this study is Carbon Dioxide (C02) emission and the independent variables are Financial Development, Economic Growth, Energy Consumption and Trade Openness. This sample of study will consists of nine developing countries which are Argentina, Brazil, China, Malaysia, Philippines, Nigeria, Russia, Qatar and Mexico from 2000 to 2014. Panel Ordinary Least Square (OLS) approach will be applied to test the relationship. The finding of this study indicates that all independent variables can be used to explain carbon dioxide (C02) emissions in developing countries. All independent variables are significant towards the study at 1% level of significance.